COVID-19 Vaccine Hesitancy in Italy: Predictors of Acceptance, Fence Sitting and Refusal of the COVID-19 Vaccination - Zarbo, Cristina; Candini, Valentina; Ferrari, Clarissa; d'Addazio, Miriam; Calamandrei, Gemma; Starace, Fabrizio; Caserotti, Marta; Gavaruzzi, Teresa; Lotto, Lorella; Tasso, Alessandra; Zamparini, Manuel; de Girolamo, Giovanni (Frontiers in Public Health, 2022)
Background: The hesitancy in taking the COVID-19 vaccine is a global challenge. The need to identify predictors of COVID-19 vaccine reluctance is critical. Our objectives were to evaluate sociodemographic, psychological, and behavioural factors, as well as beliefs, that influence COVID-19 vaccination hesitancy in the general population of Italy. Methods: A total of 2,015 people were assessed in two waves (March, April and May, 2021). Participants were divided into three groups: (1) individuals who accepted the vaccination (‘accepters’); (2) individuals who refused the vaccination (‘rejecters’); and (3) individuals who were uncertain about their attitudes towards the vaccination (‘fence sitters’). Group comparisons were performed using ANOVA, the Kruskal-Wallis test and chi-square tests. The strength of the association between the groups and the participants’ characteristics was analysed using a series of multinomial logistic regression models with bootstrap internal validation (one for each factor). Results: The ‘fence sitters’ group, when compared to the others, included individuals of younger age, lower educational level, and worsening economic situation in the previous three months. . After controlling for sociodemographic factors, the following features emerged as the main risk factors for being ‘fence sitters’ (compared with vaccine ‘accepters’): reporting lower levels of protective behaviours, trust in institutions and informational sources, frequency of use of informational sources, agreement with restrictions and higher conspirative mentality. Higher levels of COVID-19 perceived risk, trust in institutions and informational sources, frequency of use of informational sources,agreement with restrictions and protective behaviours were associated with a higher likelihood of becoming ‘fence sitters’ rather than vaccine ‘rejecters’. Conclusions: The ‘fence sitters’ profile revealed by this study is intriguing and should be the focus of public programmes aimed at improving adherence to the COVID-19 vaccination campaign.